Strategi Pemilihan Supplier Mesin Turbocharger Menggunakan Metode Analytical Hierarchy Process dan Multi-Objective Optimization Method By Ratio Analysis - Suwito, Meryna; Yuliawati, Evi (Universitas Kadiri, 2024)
The right supplier selection is an important factor for PT. Central Turbo, which is currently facing problems related to the supplier selection system that is not accurate. The study aims to develop a decision support system for the selection of turbocharger suppliers. The method used is AHP-MOORA to measure the consistency of criteria and sub-criteria in determining the highest supplier ranking. The research procedure begins with the creation of a hierarchical structure, followed by the creation of an AHP matrix to determine the weight of the criteria, the calculation of the consistency index and ratio, the normalization of the matrix, and the determination of Yi/preference value in the MOORA analysis. The decision support system developed can help PT. Central Turbo in selecting the right turbocharger supplier. This system can evaluate supplier performance more objectively and efficiently, so that it can help the company to improve its competitiveness and customer satisfaction, by considering 3 criteria, namely product performance, supplier, and service. As a result, Fencheng Xindongli Turbocharger Co., Ltd was selected as the best supplier.